2012
DOI: 10.1515/1935-1690.2452
|View full text |Cite
|
Sign up to set email alerts
|

Has the Fed Reacted Asymmetrically to Stock Prices?

Abstract: Yes. To the extent that monetary policy is assumed to react to asset prices, this reaction is usually assumed to be linear. This paper o¤ers a new perspective. I augment the model of Rigobon and Sack (2003) to allow for asymmetric reactions to stock price changes. I then demonstrate that the Federal Reserve has been following an asymmetric monetary policy rule over the period [1998][1999][2000][2001][2002][2003][2004][2005][2006][2007][2008]. While a 5% drop in the S&P 500 index is shown to increase the probab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 16 publications
(31 reference statements)
1
13
0
Order By: Relevance
“…The same result emerges in Castelnuovo and Nisticò (2010), in an estimated dynamic stochastic general equilibrium (DSGE) model where monetary policy responds to fluctuations in the stock market, and in Bjørnland and Leitemo (2009), in a VAR identified using a combination of short-run and long-run restrictions. In contrast, a more recent literature argues that the Rigobon and Sack's finding is confined to specific periods (around the 1987 stock market crash in Furlanetto (2011) and more generally around recession periods in Ravn (2012)). While those results rely on various forms of sample splitting, they may highlight some instability in the relationship between monetary policy and stock prices, thus calling for the use of a model with time-varying coefficients.…”
Section: Introductionmentioning
confidence: 93%
“…The same result emerges in Castelnuovo and Nisticò (2010), in an estimated dynamic stochastic general equilibrium (DSGE) model where monetary policy responds to fluctuations in the stock market, and in Bjørnland and Leitemo (2009), in a VAR identified using a combination of short-run and long-run restrictions. In contrast, a more recent literature argues that the Rigobon and Sack's finding is confined to specific periods (around the 1987 stock market crash in Furlanetto (2011) and more generally around recession periods in Ravn (2012)). While those results rely on various forms of sample splitting, they may highlight some instability in the relationship between monetary policy and stock prices, thus calling for the use of a model with time-varying coefficients.…”
Section: Introductionmentioning
confidence: 93%
“…Similarly, but using a combination of short-run and long-run restrictions, Bjørnland and Leitemo (2009) provide evidence that a 1% rise in real stock prices leads to an interest rate increase of close to 4 basis points. In contrast, Ravn (2012) reports that the US central bank pursued in fact an asymmetric reaction towards movements in stock prices over the period 1998-2008: while a 5% drop in the S&P 500 index increases the probability of a 25-basis-point interest rate cut by 1/3, no significant reaction of monetary policy to stock price increases can be identified. More recently, Furlanetto (2008) Other contributions are, among others, Mattesini and Becchetti (2008) who rely on a more appropriate proxy for stock price disequilibria, Dupor and Conley (2004) who focus on the 'Great Moderation' period, and Pamela (2011) who test the 'Greenspan Put' hypothesis.…”
Section: Literature Review: Do Central Banks Respond To Asset Price Dmentioning
confidence: 96%
“…The asymmetry emerged principally after the 2001 crash of the dot-com bubble where interest rates were cut extensively, but were not raised in accordance with the asset market recovery in 2003. Using a distinct econometric method (an extension of the model of Rigobon and Sack (2003)), Ravn (2012) found that the US Federal Reserve has indeed followed such a policy over the period 1998-2008: while a 5% drop in the S&P 500 index increases the probability by 1/3 of a 25-basis-point interest rate cut, no significant reaction of monetary policy to stock price increases could be identified.…”
Section: A Presumed Asymmetric Response Towards Stock Pricesmentioning
confidence: 99%
See 1 more Smart Citation
“… Empirical studies suggest that monetary policy tends to react more to declines than to increases in equity prices (Ravn, 2012;. 8 This asymmetry may thus contribute to a secular rise in wealth inequality, as equity prices are prevented from falling too much in downturns, but their increases are not tempered in booms.…”
mentioning
confidence: 99%